Bacteria and fungi community in manures before and after vermicomposting and in the horticultural substrate after use of vermicompost - Tiago, Patricia (2008)
The objective of this work was to verify the quantity of bacteria and fungi in different manures and vermicomposts produced, as well the effect of these vermicomposts used as fertilizer on the microbial community of a horticultural substrate. In the UNEMAT’s Laboratory of Microbiology the total counts of fungi and bacteria were evaluated in specific culture media. The chemical analyses of manures and vermicomposts, including organic carbon, organic material and C/N relation, were made in a certified private laboratory.  The equine manure presented the highest values of relation C/N, organic matter and organic carbon, followed by the sheep manure. These manures, equine and sheep, presented the lowest number of total microorganisms (bacteria and fungi) (2,4 x 106 UFC/g and 2,32 x 106 UFC/g). After the vermicomposting process, the quantity of bacteria predominated when compared to the number of fungi in the analyzed humus samples, except the equine humus that introduced a great fungi quantity (9,01 x 106 UFC/g),probably due to the high C/N relation (22,22). It  was verified an increase of the bacteria and fungi quantity after manuring with the different humus;  the soil fertilized with bovine humus introduced 32,96 x 106 UFC/g of bacteria and 8,26 x 106 UFC/g of fungi. So, there was difference in the total microorganisms quantity in the manure after the vermicomposting process; there was an increase of the bacteria and fungi community and in the soil fertilized with the vermicomposts there was  a significant increase of the bacteria and fungi quantity.